A Design of Innovative Development in the Industrial Types of Economic Activity - Kudryavtseva, Svetlana S.; Shinkevich, Alexey I.; Sirazetdinov, Rustem M.; Volov, Vyacheslav T.; Yusupova, Guzel F.; Torkunova, Julia V.; Khairullina, Elmira R.; Klimova, Natalya V.; Litvin, Irina Y. (International Review of Management and Marketing, 2015)
The relevance of the problem declared in the article is conditioned by the fact that the swift acceleration of changes of the existing economic and institutional terms pushes off management entities with new problems that require new approaches and methods to be solved, that in future also will accelerate innovations and modernization transformations. The aim of the article is to develop with the use of cluster analysis the innovative development model of industrial types of economic activity. The leading approach to study this problem is a design method allowing conduct the level estimation of innovative development of economic sectors with the use of quality and quantitative indexes. The method of description, comparison, cluster and descriptive analysis are used in the article. Innovative progress trends are reflected in the article, systematization of factors of innovative activity is given and the factor and descriptive analysis of industrial types of economic activity is conducted. Materials of the article have theoretical and practical significance for development of innovations' management models, as well as for development of strategy of public innovative policy. Keywords: innovation, innovative activity, cluster analysis, technological innovations, three-spiral model of innovations. JEL Classifications: O31, O34, Q01